Chapter Laser Annealing as a Platform for Plasmonic Nanostructuring - Kalfagiannis, Nikolaos (InTechOpen, 2017)
This chapter investigates the personal factors that influence intention to purchase gluten‐free products (GFPs) in Spain by non‐celiac consumers. To achieve this objective, a survey was conducted with 222 consumers in a medium‐sized Spanish town, Zaragoza, during March-April 2014 and, ordered bivariate probit model was estimated. The results suggest that intention to purchase is affected not only by self‐reported GFP knowledge but also by attitudes toward GFPs, gender, and education level.